The relationship of macroeconomic variables towards stock price volatility / Nur Shahidah Saiful Saipolbahari - Saiful Saipolbahari, Nur Shahidah (2018)
The objective of this study is to determine relationship of macroeconomic variables toward the, volatility of stock price. The price volatility of stock market is determined by several causes and it can come from various views. Several macroeconomic variables do give impact on the price volatility of stock market. The macroeconomics variables that selected to be used in this paper are the independent variables which are inflation rate, interest rate, exchange rate, and unemployment rate. The study was obtained over period year from 2013 to 2017 and based on time series data and Malaysia as the selected country. The dependent variable was measured in Malaysian Ringgit while the independent variables measured in percentage (%). The result from this study shows that exchange rate, inflation rate and unemployment rate are significance and positive relationship with the stock price volatility.